The power of art - Lewis, Richard L.; Lewis, Susan Ingalls 1949- (Boston, Massachusetts Cengage, 2019)
"Compelling and accessible, THE POWER OF ART features gorgeous images and themes that connect with today's students and an engaging writing style that's praised by instructors and students alike. The revised third edition delivers a brief yet comprehensive survey which demonstrates that art is everywhere and relevant to all students. The text incorporates global material, reflecting cultural intersections and mutual influences--and "Art News" boxes present real events, connecting art to students' lives. In addition to excellent art history coverage, THE POWER OF ART features a diverse mix of artists and spotlights current trends in artistic mediums and themes."--Provided by publisher.
Includes index.
Keywords: Art -- History